2011
DOI: 10.11606/issn.2176-7262.v44i2p177-184
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre as necessidades energéticas prescritas e administradas a pacientes em terapia nutricional enteral

Abstract: Objective: evaluating the adequacy, prescription and energy supply of enteral nutrition therapy in hospitalized patients. Methods: was performed a retrospective survey of the evolution of TNE protocol of 59 patients hospitalized in a general hospital in Marília / SP / BR. Data collected included gender, age, clinical diagnosis, anthropometric and dietary data related to the prescribed dietary formula, route and method of administration of the enteral nutrition, the daily volume prescribed and administered, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 14 publications
1
3
0
6
Order By: Relevance
“…Evidence of ingestion of the diet at a volume that is less than that which is estimated, is similar to other studies (9,13) and it is lower than another (6) , which showed higher averages, since the patients received an average of 428 ml (±243ml/day) less, i.e., they did not receive 40% of the volume prescribed (6) .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Evidence of ingestion of the diet at a volume that is less than that which is estimated, is similar to other studies (9,13) and it is lower than another (6) , which showed higher averages, since the patients received an average of 428 ml (±243ml/day) less, i.e., they did not receive 40% of the volume prescribed (6) .…”
Section: Discussionsupporting
confidence: 88%
“…The reasons for hospitalization of the patients on ENT corroborate a study in which the most frequent diagnoses were related to neurological, neoplastic and respiratory disorders (11) . Whereas other studies done on patients hospitalized in the ICU (12)(13) and hospital units (12) , showed that cardiovascular disorders were predominant.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Em um estudo realizado por Detregiachi et al (2011), com amostragem de 59 pacientes, ele encontrou entre os pacientes avaliados uma média de IMC de 21,4±6,4 kg/m2, não havendo diferença entre os sexos. A distribuição do diagnóstico nutricional, segundo este dado, foi de 54,2% dos pacientes com baixo peso, 32,2% eutróficos e 13,6% apresentavam excesso de peso.…”
Section: Resultsunclassified